Ruthenium-based metal-organic framework with reactive oxygen and nitrogen species scavenging activities for alleviating inflammation diseases. (December 2022) - Liu, Jia; Shi, Lin; Wang, Yang; Li, Mingyi; Zhou, Cheng; Zhang, Lifang; Yao, Chundong; Yuan, Ye; Fu, Daan; Deng, Yan; Liu, Miaodeng; Wang, Guobin; et al.
Abstract: The overproduction of reactive oxygen and nitrogen species (RONS) is highly associated with a variety of inflammatory diseases. Nevertheless, few treatments are clinically available to address this issue. Developing new artificial enzymes with RONS scavenging activities might be a promising strategy to treat inflammation. Here, we report a nanosized ruthenium-based metal-organic framework (Ru-MOF) with high porosity and versatile RONS scavenging activities for treating inflammatory diseases. This Ru-MOF can not only functionally mimic enzymatic activities of catalase and superoxide dismutase to remove ROS (H2 O2 and O2 - ), but also efficiently clear free radicals and RNS. Through eliminating reactive species, Ru-MOF protects cells from oxidative-stress induced damage in vitro, significantly reduces the mortality of endotoxemia mice induced by lipopolysaccharide (LPS), and markedly alleviates colon damage of the mice with colitis induced by dextran sulfate sodium (DSS). The Ru-MOF with good stability and biocompatibility as well as high catalytic activity is an effective and safe RONS-scavenger for treating inflammatory diseases. Graphical Abstract: ga1 Highlights: A ruthenium-based metal-organic framework (Ru-MOF) is developed for treating inflammatory diseases. The Ru-MOF with stable catalytic activities can simultaneously eliminate reactive oxygen and nitrogen species (RONS). The Ru-MOF possesses great biocompatibility. The Ru-MOF effectively reduces the mortality of endotoxemia mice, and alleviates clone damage of the mice with colitis.